An introduction to neural computing - Aleksander, Igor (Chapman & Hall, 1990)
Since the first edition of this book was published, much has happened in the field of neural networks. The authors reflect these changes by updating and introducing material on new developments including neurocontrol, pattern analysis and dynamic systems. This book should be useful for undergraduate students of neural networks.